2015
DOI: 10.1016/j.jaapos.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with retinal hemorrhage in suspected abusive head trauma

Abstract: PurposeTo determine risk factors associated with retinal hemorrhage (RH) in pediatric abusive head trauma (AHT) suspects.MethodsRecords of children aged 0–3 years hospitalized for suspected AHT from January 2007 to November 2011 were retrospectively reviewed in this case–control study. Children were classified into case and control groups based on RH presence. Medical history, presenting symptoms, reasons, and characteristics of injury were recorded. Logistic regression analysis was performed to identify risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
2
12
4
Order By: Relevance
“…In 2010, Thackeray et al [ 62 ] showed that among 282 children with no evidence of TBI on neuroimaging, only two (0.7%; 95% CI, 0.1–2.5) children had RH. In another study by Burkhart et al [ 7 ], the results were similar as follows: among the 168 children enrolled, 23 children (13.7%) were found to have skull or nonskull fracture without intracranial hemorrhage, and among these children, no RH was found. These findings indicate that an RH evaluation is only indicated in the presence of intracranial injury [ 7 ].…”
Section: Clinical Featuresmentioning
confidence: 58%
“…In 2010, Thackeray et al [ 62 ] showed that among 282 children with no evidence of TBI on neuroimaging, only two (0.7%; 95% CI, 0.1–2.5) children had RH. In another study by Burkhart et al [ 7 ], the results were similar as follows: among the 168 children enrolled, 23 children (13.7%) were found to have skull or nonskull fracture without intracranial hemorrhage, and among these children, no RH was found. These findings indicate that an RH evaluation is only indicated in the presence of intracranial injury [ 7 ].…”
Section: Clinical Featuresmentioning
confidence: 58%
“…By contrast, Burkhart et al. (2015) did not find that skull fractures were statistically significant predictors of RH in children ages 0–3 years. Contrary to the suggestion by Li et al.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, the variables with the strongest evidence for association with RH in our study were mSDH, GCS < 15 and occipital lobe injury. Our study also included more specific physical examination and imaging variables compared to that of Burkhart et al (2015), in addition to examining a wider age range and having a larger overall sample size. This allows the results of our study to extend to patients older than 3 years old and provides greater confidence in making clinical decisions based on findings such as long bone fractures or truncal lacerations, which the study by Burkhart et al (2015) did not directly address.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The reported incidence of retinal hemorrhage in AHT varies from 30% to more than 80%. 1316 The acute-on-chronic nature of AHT results in both acute and chronic subdural hematomas, and the repeated abuse itself can cause acute subdural hemorrhages rather than hemorrhages from spontaneous re-bleeding. Children with acute and chronic subdural hemorrhages from AHT may present with asymptomatic macrocephaly, although more severe acute intracranial hemorrhages will cause acute neurologic symptoms.…”
Section: Aht Involves Multiple Mechanisms Of Injurymentioning
confidence: 99%